2010
DOI: 10.2172/973080
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the Motion of Plasma Filaments in a Plasma Ball

Abstract: Measurements were made of the motion of the filamentary structures in a plasma ball using high speed cameras and other optical detectors. These filaments traverse the ball radially at ~10 6 cm/sec at the driving frequency of ~26 kHz, and drift upward through the ball at ~1 cm/sec. Varying the applied high voltage and frequency caused the number, length, and diameter of the filaments to change. A custom plasma ball was constructed to observe the effects of varying gas pressure and species on the filament struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Also, it was found that plasma ignition is filled the PTR reaction volume with the filaments. It has been reported that the filamentary structure depending upon the plasma ignition frequency 58 . They found that more filaments at a frequency of 10 kHz than at 1 kHz.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%
“…Also, it was found that plasma ignition is filled the PTR reaction volume with the filaments. It has been reported that the filamentary structure depending upon the plasma ignition frequency 58 . They found that more filaments at a frequency of 10 kHz than at 1 kHz.…”
Section: Experimental Setup and Methodsmentioning
confidence: 99%